The relationship between childhood trauma and romantic relationship satisfaction: the role of attachment and social support - Quan, Lijuan; Zhang, Kun; Chen, Haiyan (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the impact of childhood trauma on romantic relationship satisfaction among college students, focusing on the mediating role of attachment and the moderating role of social support.MethodsA total of 1,404 college students from Wuhu, Anqing, Chaohu, Bengbu, Fuyang, and Wuhan participated in this study. Participants completed a series of self-report questionnaires, including the Childhood Trauma Questionnaire - Short Form (CTQ-SF), the Adult Attachment Scale (AAS), the Perceived Social Support Scale (PSSS), and the Romantic Relationship Satisfaction Scale (RRSS). Demographic variables such as grade were collected to control for potential confounding factors. Statistical analyses included correlation analyses, regression models, and moderated mediation analyses using PROCESS Macro.ResultsChildhood trauma negatively predicted romantic relationship satisfaction both directly (β = -0.06, t = -2.11, p < 0.05) and indirectly through attachment (β = -0.07, t = -2.59, p < 0.05). Social support moderated the relationship between childhood trauma and attachment, with the effect of childhood trauma on attachment strengthening as social support increased (low: t = 2.18, p = 0.03; high: t = 4.37, p < 0.001). However, social support did not significantly moderate the direct effect of childhood trauma on romantic relationship satisfaction.DiscussionAttachment mediated the relationship between childhood trauma and romantic relationship satisfaction, while social support moderated the relationship between childhood trauma and attachment. These findings suggest that interventions should focus on improving attachment styles and strengthening social support to mitigate the negative effects of childhood trauma on romantic relationships.